Effects of land use change on the spatiotemporal variability of soil organic carbon in an urban-rural ecotone of Beijing, China - Hui-chun YE; Yuan-fang HUANG; Peng-fei CHEN; Wen-jiang HUANG; Shi-wen ZHANG; Shan-yu HUANG; Sen HOU (Journal of Integrative Agriculture, 2016)
Understanding the effects of land use changes on the spatiotemporal variation of soil organic carbon (SOC) can provide guidance for low carbon and sustainable agriculture. In this paper, based on the large-scale datasets of soil surveys in 1982 and 2009 for Pinggu District – an urban-rural ecotone of Beijing, China, the effects of land use and land use changes on both temporal variation and spatial variation of SOC were analyzed. Results showed that from 1982 to 2009 in Pinggu District, the following land use change mainly occurred: Grain cropland converted to orchard or vegetable land, and grassland converted to forestland. The SOC content decreased in region where the land use type changed to grain cropland (e.g., vegetable land to grain cropland decreased by 0.7 g kg−1; orchard to grain cropland decreased by 0.2 g kg−1). In contrast, the SOC content increased in region where the land use type changed to either orchard (excluding forestland) or forestland (e.g., grain cropland to orchard and forestland increased by 2.7 and 2.4 g kg−1, respectively; grassland to orchard and forestland increased by 4.8 and 4.9 g kg−1, respectively). The organic carbon accumulation capacity per unit mass of the soil increased in the following order: grain cropland soil<vegetable land/grassland soil<orchard soil<forestland soil. Therefore, to both secure supply of agricultural products and develop low carbon agriculture in a modern city, orchard has proven to be a good choice for land using.